2018
DOI: 10.3389/fncel.2018.00309
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Adhesion and Phagocytosis of Resting and Activated Microglia by Dopamine

Abstract: Microglia, the immune competent cells of the central nervous system (CNS), normally exist in a resting state characterized by a ramified morphology with many processes, and become activated to amoeboid morphology in response to brain injury, infection, and a variety of neuroinflammatory stimuli. Many studies focused on how neurotransmitters affect microglia activation in pathophysiological circumstances. In this study, we tried to gain mechanistic insights on how dopamine (DA) released from neurons modulates c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 63 publications
2
56
0
Order By: Relevance
“…CSF1R also activates Akt [11], and it induces ERK1/2-mediated signaling in microglia [9]. Akt [22,67] and ERK1/2 [19] are involved in the phagocytic process. However, the specific signaling molecules downstream of CSF1R participating in phagocytosis in microglia after brain ischemia, and the precise step(s) of the phagocytic process affected by CSFR1 remain to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…CSF1R also activates Akt [11], and it induces ERK1/2-mediated signaling in microglia [9]. Akt [22,67] and ERK1/2 [19] are involved in the phagocytic process. However, the specific signaling molecules downstream of CSF1R participating in phagocytosis in microglia after brain ischemia, and the precise step(s) of the phagocytic process affected by CSFR1 remain to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Since microglial cells reside in the CNS, they are exposed to dopamine released by dopaminergic neural circuits of the CNS. In this regard, dopaminergic signaling has been reported to modulate different microglial functions, including their inflammatory activity (Yan et al, 2015;Dominguez-Meijide et al, 2017;Elgueta et al, 2017), migration (Farber et al, 2005), and cell adhesion (Fan et al, 2018). Accordingly, microglial cells express both dopamine D1-like and D2-like receptors (Farber et al, 2005;Huck et al, 2015).…”
Section: Dopaminergic Regulation Of Microglial Cellsmentioning
confidence: 99%
“…This is the case of the DRD2, whose expression is induced upon inflammatory stimulation of microglial cells following stroke (Huck et al, 2015). High dopamine levels attenuate the inflammatory activation of microglia by reducing the release of nitric oxide (Farber et al, 2005) and decreasing the extent of phagocytosis (Fan et al, 2018). It has been suggested that this process may be mediated by the stimulation of low-affinity dopamine receptors in these cells, including DRD1 and DRD2 (Dominguez-Meijide et al, 2017), leading to a reduction in the phosphorylation of ERK1/2 (Fan et al, 2018), and to the inhibition of the angiotensin type-1/NADPH-oxidase/superoxide axis (Dominguez-Meijide et al, 2017).…”
Section: Dopaminergic Regulation Of Microglial Cellsmentioning
confidence: 99%
See 2 more Smart Citations